Increased sea-level contribution from northwestern Greenland for models that reproduce observations - Jessica A. Badgeley; Mathieu Morlighem; Hélène Seroussi (Proceedings of the National Academy of Sciences, 2025)
State-of-the-art ice sheet model simulations used in the Ice Sheet Model Intercomparison Project (ISMIP) that informs the Intergovernmental Panel on Climate Change tend to underestimate observed mass loss from the Greenland Ice Sheet, leading to the question of whether future sea-level rise may be larger than projected. We use one of these models, the Ice-sheet and Sea-level System Model, to investigate how transient calibration impacts historical and projection simulations. Transient calibration is an emerging capability in ice flow models; it uses time series of surface observations and time-dependent physics to constrain uncertain model parameters—in this case, the basal friction coefficient in the sliding law. With more constraints than the common snapshot inversion method, transient calibration has been shown to better capture trends in ice dynamics. Here, we apply both methods to northwestern Greenland, a region undergoing rapid changes. For simulations initialized with the snapshot inversion, we find that subsequent modeled velocities are generally too slow, leading to an underestimation of the mass loss. With transient calibration, however, our simulation better matches a time series of observed velocities, bringing it within observational error for mass loss; however, the fit to observed surface elevation is slightly reduced. Together with the ISMIP results, our simulations show that reproducing the high rates of historical mass loss leads to greater projected sea-level contribution from this region over the coming century. Finally, we suggest a path forward for making transient calibration scalable to the entire Greenland Ice Sheet.